Investigating the relationship between cooking time, dry matter and sensory attributes of boiled cassava - Osunbade, A.O.; Alamu, E.O.; Awoyale, W.; Adesokan, M.; Nwaoliwe, G.; Akinwande, B.; Adejuyitan, A.; Lungaho, M.; Maziya-Dixon, B. (2025)
Cassava is a major staple food in many tropical regions, but certain varieties remain hard and difficult to chew even after boiling, making them less appealing to consumers. Preferences generally lean toward cassava roots that cook quickly and possess a sweet taste. This study explored the relationship between cassava’s dry matter content and optimal cooking time (CT), specifically examining how these factors relate to sensory attributes like softness and chewability. Twenty cassava varieties, aged 10 to 12 months, were freshly harvested from the International Institute of Tropical Agriculture (IITA) research farm in Ibadan. After harvesting, the roots were peeled, washed, diced and then boiled. Standard procedures were used to evaluate each variety’s cooking time, dry matter content and sensory properties. The sensory assessment focused on the softness and chewability of the cassava roots, both are key attributes that influence consumer satisfaction. The results indicated that most sweet cassava varieties with a dry matter content above 35 % cooked within 25 minutes or less, achieving a soft texture with easy chewability. Statistical analysis using Pearson’s correlation coefficient revealed a strong positive relationship between sensory softness (r > 0.94) and chewability (r > 0.81) in varieties that had a CT of 25 minutes or less indicating that the softer a cassava variety is, the more chewable it is. This correlation underscores that dry matter content and cooking time are significant predictors of sensory quality in boiled cassava. This study emphasizes that cassava varieties with high dry matter content and shorter cooking times are not only easier to cook but are also better suited as a primary energy source in regions where cassava is a dietary staple. Consumers prefer varieties that cook quickly and have a soft, easily chewable texture, providing important insights for cassava breeding and selection programs. By focusing on these qualities, cassava breeders can develop varieties that meet consumer demands, enhancing the appeal of cassava as a food source. This research supports ongoing efforts to improve cassava quality, ensuring that it remains a versatile and desirable staple crop in the tropical regions where it plays a critical role in the diet.